Composição de Microdomínios de Membrana de Paracoccidioides brasiliensis e Histoplasma capsulatum: Importância na infectividade de macrófagos alveolares - Tagliari, Loriane [UNIFESP] (2009)
Biological membranes are constituted by a mixture of several classes of lipids. In this enviroment, sphingolipids and sterols pack tightly to form together with specific proteins a complex membrane organization known as membrane microdomains. In order to detect the presence of membrane microdomains in yeast forms of pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum, yeast forms of both fungi were lysed by vortexing with glass beads and then incubated with Brij 98 at 4ºC. Fractions containing membrane microdomains were isolated by ultracentrifugation on sucrose gradient, and their components were analyzed by HPTLC, SDSPAGE and Western blotting. Analysis of membrane lipids showed that about 40% of ergosterol from both P. brasiliensis and H. capsulatum was present in the membrane microdomains, whereas the percentage of glycosphingolipids present in P. brasiliensis and H. capsulatum was 42% and 25%, respectively. Analysis by SDS-PAGE and Western blotting clearly showed a protein enrichment in the membrane microdomains fraction of both fungi. It is noteworthy the presence of Pma1p, a fungal microdomain marker, and also the presence of a 30 kDa (glyco)protein which binds to laminin. To investigate the requirement of ergosterol to mantain the integrity of membrane microdomains, it was used methylbeta- cyclodextrin (mβCD) an agent able to efficiently extract membrane sterols. After treatment of yeasts using mβCD, it was observed the removal of 80% and 70% of ergosterol in P. brasiliensis and H. capsulatum, respectively. After treatment with mβCD it was observed a shift of 25% of the glycosphingolipids from the insoluble to the soluble fraction, conversely the distribution profile of phospholipids remained unmodified after treatment with mβCD. The protein analysis showed the displacement of a few proteins to soluble fractions of the sucrose gradient, such as Pma1p and the (glyco)protein of 30 kDa. On the other hand, using an anti-α5-integrin antibody it was detected, even after the mβCD treatment, the presence of a 50 kDa protein in membrane microdomains, suggesting the existence of microdomains that do not depend on ergosterol for their integrity. These data strongly suggest the existence of two population of microdomains: i) dependent of ergosterol for integrity maintenance of microdomains and ii) microdomains non-dependent of ergosterol for the maintenance of their functional role. Furthermore, the biological importance of membrane microdomains was clearly demonstrated by a 53% reduction of infectivity of alveolar macrophage infectivity when yeast forms of H. capsulatum were treated with mβCD.